Effect of locally-contextualized nurse-led diabetes self-management education on psychosocial health and quality of life: A controlled before-after study - Fikadu Balcha Hailu; Per Hjortdahl; Anne Moen (Elsevier, 2021)
Our study evaluated the potential of nurse-led, locally contextualized diabetes self-management education (DSME) to modify psychosocial symptoms and health-related quality of life (HRQoL) in a resource-limited setting. Thus, a controlled, two-group, before-after study was conducted among people with type 2 diabetes mellitus (T2DM). At the baseline, 116 participants were randomly assigned to the intervention, and 104 to the comparison group. The intervention consisted of six interactive DSME sessions administered by nurses for six months.At the endline, data from 78 (67%) intervention and 64 (62%) comparison group participants were included in the final analysis. Statistically, no significant differences were observed in depressive symptoms, stress, and HRQoL. Even though statistically not significant the proportion of participants who had eye examination at the endline was slightly greater in the intervention group, which is clinically significant in reducing the risk of diabetes retinopathy complication. Moreover, intervention group participants reported the DSME sessions to be helpful for the management of stress and depressive symptoms. We discuss different reasons that may explain the non-significant findings, most specifically, gaps in the adaptation of the education materials for a resource-limited setting, and modifications for low-literacy. Despite the non-significant findings in this part of our study, our overall project paved a way to design and test contextualized DSME programs in resource-limited settings of Africa.This clinical trial was retrospectively registered on ClinicalTrials.gov (Identifier: NCT03185689) on June 14, 2017. https://clinicaltrials.gov/ct2/show/NCT03185689